Rapid Diagnosis of Bacterial Infections Using Technologies Based on Nucleic Acid Detection - François J Picard; Michel G Bergeron (Canadian Journal of Infectious Diseases)
Bacterial identification and antibiotic susceptibility testing methods used in clinical microbiology laboratories generally require at least two days. This long delay often forces physicians to treat patients presumptively with broad-spectrum antibiotics. Novel diagnostic tests based on the detection of nucleic acids (DNA or RNA) offer a great potential for the rapid (approximately 1 h) diagnosis of bacterial infections. The present article reviews various aspects of the development and validation of nucleic acid-based assays suitable for the detection and identification of bacteria as well as for the detection of associated antibiotic resistance genes. The potential of these assays for routine use in clinical microbiology laboratories is also discussed.